Penggunaan Kaidah Fikih Dalam Fatwa Majelis Ulama Indonesia Tentang Keuangan Syariah - Imron Rosyadi (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
This study aims to describe and analyze the use of legal maxims of Islamic law in the fatwas of the Indonesian Ulema Council (MUI) on Islamic finance with content analysis. MUI’s fatwas on Islamic finance are amounted to 116 fatwas, using 322 items of rules. The highest number of items according to the cluster of rules which are found on the asasîyah rules are 252 items, then kullîyah rules which well agreed have 47 items, in madhhab’s kullîyah there are 17 items, and the last on special rules have 6 items. The highest number of items by category of rules are on the principle of the third asasîyah rules, 111 items, then the principle of second asasîyah rules have 63 items. From the perspective of content analysis, the use of fikih in the MUI’s fatwas on Islamic finance considers the freedom of mu`amalah to achieve a rapid progress as far as it does not endanger the businessmen and other parties. The signposts are that business should depart from good will, adapt to the traditions of its type of business, and creatively seek solutions to business problems. All matters relating to mu`amalah involve the role of policy maker to use the principle of benefit in its policy